RESPONSE OF YOUNG SOUR CHERRY TREES TO WOODCHIP MULCH AND DRIP IRRIGATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The productivity of sour cherries grown in Latvia is insufficient. Yielding of sour cherries can be advanced providing appropriate soil moisture and control of diseases. Cherry leaf spot as well as spur and twig blight are the most important sour cherry diseases which cause economical losses of the yield. The influence of woodchip mulch and drip irrigation on sour cherry yielding and resistance to the diseases is investigated. The drip irrigation and woodchip mulch increased the yield of cherries. The cultivar ‘Bulatnikovskaya’ was the most productive. Drip irrigation slightly improved resistance to cherry leaf spot for the cultivars ‘Zentenes’, ‘Orlica’ and ‘Tamaris’.